Negative gravitropic response of roots directs auxin flow to control root gravitropism. (9th May 2019) - Ge, Liangfa; Chen, Rujin
Abstract: Root tip is capable of sensing and adjusting its growth direction in response to gravity, a phenomenon known as root gravitropism. Previously, we have shown that negative gravitropic response of roots ( NGR ) is essential for the positive gravitropic response of roots. Here, we show that NGR, a plasma membrane protein specifically expressed in root columella and lateral root cap cells, controls the positive root gravitropic response by regulating auxin efflux carrier localization in columella cells and the direction of lateral auxin flow in response to gravity. Pharmacological and genetic studies show that the negative root gravitropic response of the ngr mutants depends on polar auxin transport in the root elongation zone. Cell biology studies further demonstrate that polar localization of the auxin efflux carrier PIN3 in root columella cells and asymmetric lateral auxin flow in the root tip in response to gravistimulation is reversed in the atngr1;2;3 triple mutant. Furthermore, simultaneous mutations of three PIN genes expressed in root columella cells impaired the negative root gravitropic response of the atngr1;2;3 triple mutant. Our work revealed a critical role of NGR in root gravitropic response and provided an insight of the early events and molecular basis of the positive root gravitropism. Abstract : Early events of the gravitropic response of plant roots are still not well understood. Here, we show that previously reported negative gravitropism of Arabidopsis atngr1;2;3 triple mutant depends on root columella cell‐expressed auxin efflux carrier PIN3, PIN4, and PIN7 genes. Our cellular and genetic results indicate that the plasma membrane‐localized NGR proteins direct polar localization of PIN proteins and asymmetric auxin flow in the root tip to control root gravitropic response. Thus, our work uncovers the regulatory mechanism of NGR proteins in an early event of root gravitropism.